Clinical Results After Precision Pulse Capsulotomy - Gundersen, Kjell G (Clin Ophthalmol, 2020)
PURPOSE: To compare residual refractive error and complication rates between eyes undergoing a manual capsulotomy and those receiving a precision pulse capsulotomy using an automated device. PATIENTS AND METHODS: This study was a non-interventional two-arm retrospective chart review of clinical results after bilateral cataract surgery or refractive lens exchange (RLE) surgery with a monofocal toric intraocular lens (IOL) or a trifocal IOL where a manual capsulorhexis (Manual) or automated precision pulse capsulotomy (PPC) was performed. RESULTS: Exams from 243 eyes (122 PPC, 121 Manual) from 124 patients were reviewed; about 75% of which had a trifocal IOL implanted. There was no statistically significant difference in the MRSE with either IOL type, or overall. The overall percentage of eyes with residual refractive cylinder ≤ 0.50 D was significantly higher in the PPC group (89% vs. 79% in the manual group, p = 0.03), primarily driven by results with the toric IOL. Best corrected distance visual acuity was not statistically significantly different by group. Capsulotomy-related complications were lower in the PPC group relative to the manual group (4.1% vs. 6.6%), but this result was not statistically significant (p = 0.38). CONCLUSION: Significantly more eyes had refractive cylinder ≤0.50 D in the PPC group. For all other measures, the automated PPC device produced clinical results equivalent to those achieved with a manual capsulorhexis.